Study on Varying Salt Level and Storage Time on Physico-Chemical and Sensory Quality of Beef Nugget (Progressive Agriculture, 2014)
The experiment was conducted to find out the effect of salt and storage temperature on the physico-chemical properties of beef nugget. For this purpose nugget samples were divided into two parts; one is called fresh nugget and another is preserved nugget at different temperatures. Then the fresh samples as well as the preserved samples were divided into four subdivisions. Then these are treated with different salt levels (0, 1.5, 3 and 5% salt level). The preserved samples were stored at 4oC and -20oC. Samples preserved at 4oC were stored in the refrigerator for 21 days and were analyzed on 7th day, 14th day and 21th day and samples preserved at -20oC were stored in the refrigerator for 60 days and were analyzed on 15th day, 30th day, 45th day and 60th day of preservation. Dry matter and Ash content of all the samples increased significantly (P